2012
DOI: 10.1534/genetics.112.139667
|View full text |Cite
|
Sign up to set email alerts
|

V-ATPase V1 Sector Is Required for Corpse Clearance and Neurotransmission in Caenorhabditis elegans

Abstract: The vacuolar-type ATPase (V-ATPase) is a proton pump composed of two sectors, the cytoplasmic V 1 sector that catalyzes ATP hydrolysis and the transmembrane V o sector responsible for proton translocation. The transmembrane V o complex directs the complex to different membranes, but also has been proposed to have roles independent of the V 1 sector. However, the roles of the V 1 sector have not been well characterized. In the nematode Caenorhabditis elegans there are two V 1 B-subunit genes; one of them, vha-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 74 publications
0
18
0
Order By: Relevance
“…To investigate the effect of impaired V-ATPase function in neurons, we examined mutants defective in the V-ATPase subunit UNC-32, which is required for synaptic vesicle acidification [25, 26], using the FLP-3::Venus and IDA-1::GFP reporters described above. unc-32 mutants had low neuropeptide levels and high IDA-1::GFP levels at synapses, molecular defects similar to those of vps-50 mutants (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the effect of impaired V-ATPase function in neurons, we examined mutants defective in the V-ATPase subunit UNC-32, which is required for synaptic vesicle acidification [25, 26], using the FLP-3::Venus and IDA-1::GFP reporters described above. unc-32 mutants had low neuropeptide levels and high IDA-1::GFP levels at synapses, molecular defects similar to those of vps-50 mutants (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…SpH is a fusion of the synaptic-vesicle protein synaptobrevin with the pH-sensitive GFP reporter pHluorin, and the pHluorin moiety is localized to the vesicular lumen, where it can be used to assay vesicle pH [27, 28]. SpH has been used to study the effects of mutations in the V-ATPase complex on C. elegans GABAergic neurons [25]. vps-50 mutants, like unc-32 mutants, showed increased SpH fluorescence, indicating that vps-50 mutants are defective in vesicle acidification (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Acidification of lysosomal lumen is important for apoptotic cell degradation. Inactivation of the vacuolar H ATPase 12 (vha-12) gene encoding the V1 B subunit of the lysosomal proton pump vacuolar-type ATPase (V-ATPase), impairs the degradation of apoptotic cells (Ernstrom et al 2012).…”
Section: Acidification Of Phagosomal Lumenmentioning
confidence: 99%
“…The C. elegans genome encodes 21 V-ATPase subunits (see Figure 1A of the accompanying article in this issue by Ernstrom et al 2012), and we examined their expression and RNA interference characteristics (see http://www. wormbase.org/, Jiang et al 2001, andReinke et al 2000).…”
Section: V-atpase Mutant That Specifically Affects Spermatogenesismentioning
confidence: 99%
“…We examined the microarray data for the 21 V-ATPase subunits encoded by Caenorhabditis elegans and found that there are two B-subunit paralogs with strikingly different patterns of expression (Reinke et al 2000;Jiang et al 2001). While the X chromosome-located vha-12 gene showed somatic expression and the accompanying article in this issue by Ernstrom et al (2012) shows the null phenotype of this gene to be lethal, the second gene encoding a B subunit showed upregulated expression during spermatogenesis. We used positional cloning techniques to show that the previously described spe-5 gene, which is on chromosome I (Machaca and L'Hernault 1997), encodes this spermexpressed B subunit.…”
mentioning
confidence: 99%